Case report: Fibrotic interstitial lung disease as the initial manifestation of hereditary pulmonary alveolar proteinosis caused by CSF2RB mutation - Li, Qiuhong; Xie, Huikang; Li, Manhui; Cheng, Kebin (Frontiers in Pharmacology, 2024)
A 50-year-old male was admitted to the hospital with a 3-year history of dyspnea and cough. Chest high-resolution computed tomography (HRCT) did not show typical features of pulmonary alveolar proteinosis (PAP), but rather atypical features of interstitial lung disease with fibrosis. The diagnosis of PAP was confirmed through transbronchial lung cryobiopsy. Whole exome sequencing identified a rare homozygous frame shift mutation (c.304_305del:p.S102Ffs*5) in exon 3 of the CSF2RB gene in our patient. This case represents a rare occurrence of fibrotic interstitial lung disease in PAP.